Interaction among funding liquidity, liquidity creation and stock liquidity of banks: Evidence from BRICS countries. Issue 4 (14th November 2016) - Umar, Muhammad; Sun, Gang
Abstract : Purpose: This study aims to explore the relationship between three different kinds of bank liquidity: funding liquidity; liquidity creation; and stock liquidity. Design/methodology/approach: It used the data from listed banks of BRICS countries spanning the period 2007-2014. Simultaneous equations model and three-stage least square estimation were used for analysis. Findings: First of all, increase in liquidity creation is linked to decline in funding liquidity, but variation in funding liquidity does not describe changes in liquidity creation. Second, higher stock illiquidity is associated with greater liquidity creation, but liquidity creation does not determine variation in stock liquidity. Lastly, there is no direct relationship between funding liquidity and stock liquidity; however, stock liquidity indirectly affects funding liquidity through liquidity creation. Practical implications: The findings highlight the fact that capital is not the only determinant of liquidity creation, rather stock liquidity is an equally important determinant in the case of listed banks of BRICS countries. This fact has been highlighted by the recent financial crisis. Furthermore, funding liquidity depends on liquidity creation which depends on stock liquidity. However, the stock liquidity of banks neither depends on liquidity creation nor funding liquidity. Originality/value: To the best of the authors' knowledge, this study is the first one to provide the empirical evidence for the relationship between three different kinds of bank liquidity.